(untitled) (Fiep Bulletin - online, 2011)
This text presents the form as the thematic axis "Gymnastics" is proposed in the Pedagogical Project of Physical Education from school Santo Belo Horizonte’s Little august. For being a present corporeal practice since the Infantile Education to the 3rd year of the Average Teaching proposed us to do an experience report on the ways that we thrash when changing the pedagogical treatment that I had been given to the gymnastics, as mere activity, for an approach that is supported in a literature criticizes of the Physical Education.